Hormonal Receptors and Human Epidermal Growth Factor Receptor 2 Discordance between Primary and Recurrent Breast Cancer in Sample of Iraqi Patients - Muna K. Zaweer; Azhar S. Alzubaidi (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Though progesterone receptor and estrogen receptor are weak prognostic indicators,they are greatly predictive of response to endocrine therapy. HER2 overexpression or amplification is apowerful predictive factor for response to specific systemic therapies. Variation in estrogen receptor (ER),progesterone receptor (PR), and HER2 status between primary breast carcinoma and subsequent relapse ofis clearly recognized. Aim of study: The study aims at determining the rate of discordance in progesteronereceptor, estrogen receptor and human epidermal growth factor receptor 2 status between primary tumor andsubsequent locoregional and metastatic disease in a sample of patients attend oncology teaching hospital.Patients and Methods: A retrospective study conducted included 80 females patients attending oncologyteaching hospital between December 2013 – December 2017 for whom the ER,PR,and HER2 status wereknown on tissue samples of both primary and subsequent locoregional and metastatic disease .Results: The ER,PR,and HER2 status discordance rate for between primary breast cancer and subsequentlocoregional relapse and distant metastasis was 27.5%, 42.5% and 22.5% respectivelyConclusion: The rate of discordance in ER and PR status primary and relapsed breast carcinoma in patientsmanaged at oncology teaching hospital was similar to other studies. While the rate of discordance for HER2status between primary and relapsed breast carcinoma was slightly higher than international studies.